Making Movies - Lumet, Sidney (London Bloomsbury Publishing, 1996)
From one of America's most acclaimed directors comes a book that is both a professional memoir and a definitive guide to the art, craft, and business of the motion picture. Drawing on 40 years of experience on movies ranging from Long Day's Journey Into Night to The Verdict, Lumet explains the painstaking labor that results in two hours of screen magic.
Includes Index
Keywords: Movie